Sand drift encroachment in the Dunhuang Mogao Grottoes District and its control - 屈建军 董光荣 文子祥 张伟民 胡世雄 (Science China. Earth sciences, 1997)
Analysis on sand drift damages to the Dunhuang Mogao Grottoes showed that the actual sand drift hazards in the area are mainly attributed to the gobi wind-sand stream formed by sand coming from the Mingsha Mountain (megadune), while the migration of the megadune and its frontal edge dunes is actually not a major threat to the grottoes. The gobi belt on the cliff top of the Mogao Grottoes is not only a natural sand transport field but also a natural protective screen which prevents the megadune and its frontal edge dunes from advancing towards the grottoes or burying the grottoes. Therefore efforts to protect the Mogao Grottoes should be focussed on halting the gobi wind-sand stream rather than on checking the migration of sand dunes. For this reason, effective sand blockade and stabilization measures should be adopted at the frontal edge of the megadune but no sand retarding works are allowed to be set up in the gobi belt so as to avoid sand accumulation and entering the grottoes.